2018
DOI: 10.1002/acp.3479
|View full text |Cite
|
Sign up to set email alerts
|

Are seductive details seductive only when you think they are relevant? An experimental test of the moderating role of perceived relevance

Abstract: SummaryWe investigated whether seductive details (i.e., interesting but irrelevant adjuncts) are harmful to learning only when students (mistakenly) think that they are relevant. We therefore conducted a study in which participants (N = 86) learned either without seductive details (control condition) or with seductive details—in the latter case with or without being informed about the seductive details' irrelevance. In line with our hypotheses, only participants who were not informed about the irrelevance of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 35 publications
7
55
3
Order By: Relevance
“…Regarding reliability, beyond the overall Cronbach's alpha of .64, the survey also presented moderate Cronbach's alphas in each type of CL (ICL α = .71; GCL α = .71; ECL α = .69). These findings are similar to those found by Eitel, Bender, and Renkl (2019) on ICL ( α = .77) and ECL ( α = .71; p. 24). In relation to validity, a correlation analysis between the traditional CL measures and the new instrument revealed a significant moderate correlation ( r = .63, p < .001).…”
Section: Limitationssupporting
confidence: 91%
“…Regarding reliability, beyond the overall Cronbach's alpha of .64, the survey also presented moderate Cronbach's alphas in each type of CL (ICL α = .71; GCL α = .71; ECL α = .69). These findings are similar to those found by Eitel, Bender, and Renkl (2019) on ICL ( α = .77) and ECL ( α = .71; p. 24). In relation to validity, a correlation analysis between the traditional CL measures and the new instrument revealed a significant moderate correlation ( r = .63, p < .001).…”
Section: Limitationssupporting
confidence: 91%
“…The effect would happen because the irrelevant elements capture attention, and load working memory (Sanchez & Wiley, 2006; Wiley et al, 2014). Eitel et al (2019) found negative effects of seductive details on learning outcomes in a condition in which students were not informed about the irrelevance of seductive details, compared to students warned about it, arguing that the irrelevant information distract attention from relevant information. Studies with eye‐tracking (Alemdag & Cagiltay, 2018; Korbach et al, 2017; Park et al, 2015; Tsai et al, 2019) have supported the attentional explanation.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Eitel et al ( 2019 ) could also shed some light on the effectiveness of learner-managed redundancy, but it needs to be noted that the redundancy effect was confounded with the signaling principle in this study. Eitel and colleagues investigated three groups of adult learners studying a booklet about the steps in the formation of lightning.…”
Section: Comparing the Effects Of Instructor-managed Versus Learner-mmentioning
confidence: 89%
“…Redundancy can also occur when lessons are unnecessarily elaborated, such as textbook chapters that contain many details in addition to the core concepts (e.g., Eitel et al, 2019 ; Harp & Mayer, 1998 ). In a study by Mayer et al ( 1996 ), undergraduates studied learning materials about lightning and then completed recall and transfer tests.…”
Section: Problem: Materials Contains Redundant or Nonessential Informamentioning
confidence: 99%